EFFICACY OF IMPLEMENTATION OF PANCHAYAT JAGRATA SAMITI: A CASE STUDY OF KOZHIKODE DISTRICT, KERALA (INDIA) - Subair, K (International Journal of Research -GRANTHAALAYAH, 2017)
The State and Central Governments have time to time enacted legal provisions and there are lot of enforcement mechanisms to protect and prevent women and girls from the violence, but when it comes to implementation it may not work properly due to various reasons. Panchayat Jagrata Samiti (PJS) is one of the mechanisms to protect the rights of women which are considered as the prototype of Kerala Women’s Commission. It has been built for attaining gender equality, equity and justice. PJS is for working dynamically by replying to complaints related to violation of women’s rights along with engaging moves to safeguard the security and safety of women. It is needed for addressing the strategic needs of women for their empowerment to be practicalised in the social life situations. PJS has social responsibility to mainstreaming and upbringing gender equality in the process of decentralisation which leads to enrichment of women’s status in society. This particular study tries to understand the efficacy of implantation of PJS in Kozhikode district (Kerala) and the engagements of various stakeholders. This study tries to analyse the role of PJS for protecting the rights of women and giving justice to them. This study is qualitative in methodology. The primary data is collected through semi-structured interviews, content analysis of policy documents and media reports.